1996
DOI: 10.1128/cdli.3.5.601-604.1996
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and gentle method for isolation of genomic DNA from pathogenic Nocardia spp

Abstract: The lack of simple and efficient methods for extraction of DNA from Nocardia spp. has hampered molecular manipulation of the DNA for diagnostic purposes. In the present study, a method for the rapid extraction of undegraded genomic nocardial DNA was established. Briefly, 14 pathogenic Nocardia strains were grown at 37؇C for 3 to 5 days in Sauton broth containing 0.05% Tween 80. Subsequently, the cultures were treated for 48 h with 1.2 mg of cycloserine per ml (final concentration). Cells were then harvested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Other procedures for DNA extraction from the genus Nocardia are expensive and time-consuming. [ 12 13 14 ] Loeffelholz and Scholl in 1989 established a difficult method for DNA extraction from Nocardia species. This procedure was time-consuming and monotonous.…”
Section: Resultsmentioning
confidence: 99%
“…Other procedures for DNA extraction from the genus Nocardia are expensive and time-consuming. [ 12 13 14 ] Loeffelholz and Scholl in 1989 established a difficult method for DNA extraction from Nocardia species. This procedure was time-consuming and monotonous.…”
Section: Resultsmentioning
confidence: 99%
“…This method has been used previously to extract DNA from rapid-growing mycobacterial strains and nocardia species, which share the cell wall characteristics of mycobacteria. 24,34 The M. avium Hsp65 bore a striking similarity to the homologous proteins from other mycobacterial species, showing a 93% amino acid homology with the pathogenic M. tuberculosis and a higher 97% similarity to M. paratuberculosis, which is now considered to be part of the M. avium complex. There was also almost 50% homology with human and murine homologues.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are more than 100 described species of Nocardia, with 30 of these being important to humans (Brown-Elliott et al, 2006;Betrán et al, 2016;Lebeaux et al, 2019). The use of molecular techniques, such as amplification by polymerase chain reaction (PCR) of the gene encoding RNA of ribosome subunit 16 (Torres et al, 1996;Kandi, 2015) has allowed new species to be identified or existing species to be differentiated (Conville et al, 2000). These different species have already been found in domestic animals (Biberstein et al, 1985;Emeruwa, 1986 The number of reported cases of nocardiosis has gradually increased worldwide.…”
Section: Introductionmentioning
confidence: 99%